Urgent problems of differentiation of the ukraine's legislating closes close to the sense, regulating social protection of policeman - Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Topical issues of the development of modern science. Abstracts of the 3rd International scientific and practical conference (13-15 nov. 2019, Sofia). - Bulgaria, Sofia. Publishing House «ACCENT», 2019. - P. 70-74, 2019)
На основі детального аналізу законодавства України, що регулює соціальний захист працівників поліції, автор уточнив причини виплати одноразових надбавок поліцейським або їхнім родинам, а також розмежував поняття «служба в поліції» та «виконання службових обов'язків, пов'язаних із виконанням повноважень та основних завдань поліції».

Based on a detailed analysis of the legislation of Ukraine governing the social protection of police officers, the author clarified the reasons for paying lump-sum allowances to police officers or their families, as well as differentiated the concepts of «serving in the police» and «performing official duties related to the fulfillment of the powers and main tasks of the police».

На основе детального анализа законодательства Украины, регулирующего социальную защиту работников полиции, автор уточнил причины выплаты одноразовых надбавок полицейским или их семьям, а также разграничил понятия «служба в полиции» и «выполнение служебных обязанностей, связанных с исполнением полномочий и основных задач полиции».
Keywords: National Police of Ukraine; social protection; policeman; lumpsum allowance; disability; injuries; police service; performance of official duties; Національна поліція України; соціальний захист; поліцейський; одноразова допомога; інвалідність; поранення; служба в поліції; виконання службових обов'язків